Temperature Field Determination during Bridge Pier Construction - Phung, Ba-Thang; Nguyen, Trong Chuc (Engineering, Technology & Applied Science Research, 2025)
Thermal deformation resulting from the hydration of cement in the concrete mix is a primary cause of thermal cracking in structures, particularly in mass concrete elements, and more specifically in the abutments and piers of bridges. These cracks are most likely to occur at an early age, when the temperature rise within the concrete is most pronounced. The formation of thermal cracks is especially problematic in the early stages of construction, as the temperature differential between the interior and surface of the structure can lead to significant stresses. Therefore, understanding the temperature and stress fields during the construction of bridge piers is crucial for identifying effective strategies to mitigate thermal cracking. This paper investigates the underlying causes of thermal crack formation in bridge piers and applies the Finite Element Method (FEM) to analyze the temperature field during the construction process under typical Vietnamese conditions. The findings of this study aim to provide practical solutions for preventing thermal cracking in bridge pier structures during the construction phase, ensuring the durability and integrity of the bridge over time.